-6x+3(-11x-7)=9-3(11x-8)

Simple and best practice solution for -6x+3(-11x-7)=9-3(11x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+3(-11x-7)=9-3(11x-8) equation:


-6x+3(-11x-7)=9-3(11x-8)

We simplify the equation to the form, which is simple to understand
-6x+3(-11x-7)=9-3(11x-8)

Reorder the terms in parentheses
-6x+(-33x-21)=9-3*(11x-8)

Remove unnecessary parentheses
-6x-33x-21=+9-3+*(+11x-8+)

Reorder the terms in parentheses
-6x-33x-21=9+(-33x+24)

Remove unnecessary parentheses
-6x-33x-21=+9-33x+24

We move all terms containing x to the left and all other terms to the right.
-6x-33x+33x=+9+24+21

We simplify left and right side of the equation.
-6x=+54

We divide both sides of the equation by -6 to get x.
x=-9

See similar equations:

| .7y-1.5y=-35 | | 11x+3x=-9(x+9)+8(6x+7) | | -8+-6(-z+6)= | | 81x^2-5=139 | | 5r^2-2=403 | | 9p^2-1=899 | | 3(7+6u)+5u= | | 7m^2+12m+1=0 | | 4m^2-12=-8 | | x/2+3x/4=8 | | 6+10(5+10p)= | | 2(5-3u)+9u=28 | | 10n^2+6=166 | | -2x+24=x+6 | | 9(9s+2)= | | -4+11(10x+4)=-2x+9(1+9x) | | 34*1.125t=143 | | 0.33(2x-3)=0.75(2-4x) | | 9(-10w+-5)= | | 6+16a^2=106 | | 5(-3d+-5)= | | 0.3(2x-3)=0.75(2-4x) | | 23x-7x+4x=0 | | p(5)=7x-3 | | 8-5x+6x=10 | | 2(5x-4)=6x+2 | | .85+.8-x=2.4 | | 1.99b=68.88 | | 7(8k+1)+4k= | | 8+7(5-3c)+4c= | | x^2+15x-16= | | 72+7d=15 |

Equations solver categories